2016
DOI: 10.1177/1557988316629641
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Persian Translation of the Sexual Quality of Life–Male Questionnaire

Abstract: Sexual dysfunction has been demonstrated to be related to a poor quality of life. These dysfunctions are especially prevalent among men. This cross-sectional study aimed to investigate the psychometric properties of the Persian translation of the Sexual Quality of Life-Male (SQOL-M), translated and adapted to measure sexual quality of life among Iranian men. Forward-backward procedures were applied in translating the original SQOL-M into Persian, and then the psychometric properties of the Persian translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…However, previous research has implied a significant relationship between WAI and quality of life ( Milosevic et al, 2011 ). Furthermore, Maasoumi et al (2017) suggested that there is a significant relationship between the WAI and the sexual quality of life in men. A reason behind this may be the two-way relationship existing between the WAI and the quality of life and sexual quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has implied a significant relationship between WAI and quality of life ( Milosevic et al, 2011 ). Furthermore, Maasoumi et al (2017) suggested that there is a significant relationship between the WAI and the sexual quality of life in men. A reason behind this may be the two-way relationship existing between the WAI and the quality of life and sexual quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The IIEF-15 was compared with a single-item self-assessment of ED, 19 the Patient Reported Outcomes Measurement Information System, 23 Quality Erection Questionnaire, 27 Erection Hardness Score, 20,24,27,33 Sexual Experience Questionnaire, 30 Male Genital Self-Image Scale, 39 Female Assessment of Male Erection, 38 partnership satisfaction, 43 Hypogonadism Impact of Symptoms Questionnaire Short Form, 25 Sexual Quality of LifeeMale , 29 Sexual Modes Questionnaire, 31 Inflammatory Bowel Disease Male Sexual Dysfunction Scale, 32 Beliefs About Sexual Functioning Scale, 34 Premature Ejaculation Tool, 41 and clinician ratings. 1,38,43 The methodologic quality was rated as "adequate" 1,23,27,29,31,32,34,38,39,41,43 or "doubtful". 19,20,24,25,33 The doubtful ratings were due to a small number ("other flaws" in COSMIN methodologic quality), 33 use of the Pearson correlation where the Spearman correlation should have been used, 24 imprecise reporting of hypotheses ("other flaws" in COSMIN methodologic quality), 25 the lack of information on measurement properties of the comparator instrument, 19 or imprecise reporting of results.…”
Section: Convergent Validitymentioning
confidence: 99%
“…A total of 417 heart patients referred to the hospital during the one year of study were enrolled into the research. It should be noted that the sample size was 4-10 times more than the number of items in the questionnaire to analyze the factors structure [10]. Given the number of items in the questionnaire, the number of participants was suitable for evaluating its psychometric properties.…”
Section: Research Design and Populationmentioning
confidence: 99%
“…CFA allows models to be used both statistically and theoretically, which is not possible by conventional multivariate methods such as Exploratory Factor Analysis (EFA) [16]. It should be noted that the appropriate sample size for factor analysis is 4 to 10 times more than the number of variables and at least 100 [10]. To determine the construct validity in the current investigation, the questionnaire was distributed among 417 heart patients with a history of exposure to dust.…”
Section: Construct Validitymentioning
confidence: 99%
See 1 more Smart Citation